2000
DOI: 10.1002/(sici)1097-0215(20000215)85:4<492::aid-ijc8>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity in sporadic melanomas as revealed by loss‐of‐heterozygosity analysis

Abstract: The major obstacle preventing effective treatment of melanoma is the biological heterogeneity of tumor cells. This study was performed to determine clonal genetic heterogeneity within primary melanoma and the evolution of these heterogeneous sub‐clones during disease progression. DNA samples were obtained from 44 morphologically distinct areas identified within 10 primary tumors and from 15 metastases in the same patients. Loss of heterozygosity (LOH) analyses were performed using 17 microsatellite markers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…We looked at the variability of pigmentation within a lesion and found that heterogeneity of pigmentation more often was associated with a malignant histology compared with a uniform pigmentation. This perhaps reflects increasing cellular heterogeneity associated with malignant progression resulting in clones of tumour cells with divergent phenotypic features associated with the variable accumulation of genetic errors 23. New angiographic techniques with improved transmission through melanin such as indocyanine green combined with confocal image analysis may have potential implications for more precise evaluation of these features in clinical practice 26…”
Section: Discussionmentioning
confidence: 99%
“…We looked at the variability of pigmentation within a lesion and found that heterogeneity of pigmentation more often was associated with a malignant histology compared with a uniform pigmentation. This perhaps reflects increasing cellular heterogeneity associated with malignant progression resulting in clones of tumour cells with divergent phenotypic features associated with the variable accumulation of genetic errors 23. New angiographic techniques with improved transmission through melanin such as indocyanine green combined with confocal image analysis may have potential implications for more precise evaluation of these features in clinical practice 26…”
Section: Discussionmentioning
confidence: 99%
“…Due to these different tumor subclones within a patient (intra-patient heterogeneity), it is believed that diverse resistance mechanisms can co-exist within one patient [17, 5]. However, where these resistance mechanisms originate from and how they evolve under treatment remains poorly understood [6, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic heterogeneity of cancer cells within a patient can potentially contribute to treatment resistance and the high rate of recurrence, and represents a major challenge for personalized cancer therapy. In melanoma, genomic heterogeneity has been observed among tumors in a single patient (68), but also at separated locations within individual tumors (9). This inter- and intra-tumoral heterogeneity, which has been demonstrated also in other solid tumors (10,11), reflects the evolutionary complexity that tumor cells display under specific microenviromental and therapeutic pressures during the course of the disease (5,7,11).…”
Section: Introductionmentioning
confidence: 99%